Wage Inequalities and Low Pay: The Role of Labour Market Institutions - Claudio Lucifora (Fondazione Eni Enrico Mattei (FEEM), 1999)
In this study, we investigate the role that some institutional features play in shaping the distribution of wages across a number of OECD countries. While considerable attention has been devoted in recent years to the evolution of earnings inequality and to the analysis of the competing explanations for the observed phenomena, also the existence (and persistence) of considerable structural differences - across countries - in the level of wage inequality and the incidence of low pay can shed some light on a different dimension of inequality patterns. In particular, we focus on three specific features: the effects of trade unions, the structure of collective bargaining and the existence of regulations on wages. By looking at the different moments of the distribution of earnings various dimensions of low pay have been analysed, namely the effects of the institutional setting on the mean, the dispersion and the (time) covariance of earnings. Consistent with previous work, our results suggest that institutions are a relevant factor in shaping the distribution of earnings and the incidence of low pay. We show that institutional settings differ substantially across countries and that institutional variety in the labour market is able to explain a great deal of the observed patterns in low pay across countries.
Keywords: J3; J5; P5; 330; Wage inequality; Low wage employment; Labour market institutions; Lohndifferenzierung; Niedriglohn; Institutionalismus; Tarifpolitik; Lohnpolitik; OECD-Staaten